Influence of mode of delivery on infant gut microbiota composition: a pilot study - Li Yu; Yong Guo; Jie-Ling Wu (Journal of Obstetrics and Gynaecology)
Background Microbial colonisation in infants is initially dependent on the mother and is affected by the mode of delivery. Understanding these impacts is crucial as the early-life gut microbiota plays a vital role in immune development, metabolism, and overall health. Early-life infant gut microbiota is diverse among populations and geographic origins. However, in this context, only a few studies have explored the impact of the mode of delivery on the intestinal microbiome in children in Guangzhou, China. Therefore, this study aimed to investigate the influence of birth mode on the intestinal microbiota of healthy infants in Guangzhou, China.Methods Faecal samples were collected once from 20 healthy full-term infants aged 1–6 months, delivered via either caesarean section (CS) or vaginal delivery (VD), post-enrolment. The intestinal microbiota were characterised using full-length 16S rRNA gene sequencing. Bacterial quantity and community composition were compared between the two groups.Results No significant differences in gut bacterial diversity and richness were observed between the CS and VD groups. The Pseudomonadota phylum (44.15 ± 33.05% vs 15.62 ± 15.60%, p = 0.028) and Enterobacteriaceae family (44.00 ± 33.11% vs 15.31 ± 15.47%, p = 0.028) were more abundant in the CS group than in the VD group. The VD group exhibited a higher abundance of the Bacillota phylum (40.51 ± 32.77% vs 75.57 ± 27.83%, p = 0.019),Conclusions The early stage of intestinal bacterial colonisation was altered in the CS group as compared with the VD group. Our findings provide evidence that CS has the potential to disrupt the maturation of intestinal microbial communities in infants by influencing the colonisation of specific microorganisms. Further comprehensive studies that consider geographical locations are necessary to elucidate the progression of microbiota in infants born via different delivery modes.